Given: x2 - 6x + 3 = 0
x2 - 6x = - 3
x2 - 2.x.3 + 32 = - 3 + 32 (adding 32 on both sides)
(x - 3)2 = - 3 + 9 = 6 using a2 - 2ab + b2 = (a - b)2
(taking square root on both sides)
Hence the roots of equation are
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation